ANALISIS PENDAPATAN USAHATANI PADI SAWAH METODE TANAM BENIH LANGSUNG DI DESA ASTINA KECAMATAN TORUE KABUPATEN PARIGI MOUTONG - Erma Susanta,Made Antara,Effendy, I Wayan (AGROTEKBIS, 2016)
The aim of this research is to know the total Income and the feasibility of this rice field farming with Direct Seeding Methode in Astina Village Torue Subdistrict Parigi Moutong Regency.This research started on May until April 2015.Respondents in this research amount to 30 houshold. Determination of respondent used simple random sampling while the analytical data tools were Income and feasibility analysis. The results showed total income was Rp1,346,798/ha with avernge total cost Rp 9,186,263/ha. The result of feasibility analysis showed that rice farming with directed seeding methode can be categoried fiasible with ratio of 2.2.